2005
DOI: 10.1002/chin.200509029
|View full text |Cite
|
Sign up to set email alerts
|

tert‐Amino Effect in Heterocyclic Chemistry. Synthesis of Hydrogenated Spiro Derivatives of Quinolines.

Abstract: Ring closure reactions O 0130tert-Amino Effect in Heterocyclic Chemistry. Synthesis of Hydrogenated Spiro Derivatives of Quinolines. -The synthesis of spiro derivatives of heterocycles is based on reactions proceeding by the mechanism of the "tert-amino-effect" which generalizes cyclization reactions of certain derivatives of ortho-substituted N,N-dialkylanilines. Using this strategy, a variety of spiro compounds is obtained by reaction of o-aminobenzaldehydes (III) with cyclic CH-active compounds such as (IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…We investigated the three-component condensation of thiourea, ethyl acetoacetate, and p-substituted benzaldehyde derivatives in the Biginelli reaction either at the simple heating or microwave irradiation. If the reaction is carred out in the boiling ethyl alcohol using MnCl 2 ·H 2 O as a catalyst, it is completed within 6-8 h. The use of microwave irradiation makes it possible to reduce the reaction time to 150 min at 750 W. The structure of the obtained 5-(ethoxycarbonyl)-4-(4-R-phenyl)-6-methyl-3,4-di-hydropyrimidine-2(1H)-thiones I-III) was confirmed by the analytical and spectral data, which were consistent with those of the other 3,4-dihydropyrimidinethiones [1][2][3]. Thus, the behavior of the reaction components under the microwave irradiation conditions does not differ from that under the conventional heating conditions.…”
supporting
confidence: 71%
“…We investigated the three-component condensation of thiourea, ethyl acetoacetate, and p-substituted benzaldehyde derivatives in the Biginelli reaction either at the simple heating or microwave irradiation. If the reaction is carred out in the boiling ethyl alcohol using MnCl 2 ·H 2 O as a catalyst, it is completed within 6-8 h. The use of microwave irradiation makes it possible to reduce the reaction time to 150 min at 750 W. The structure of the obtained 5-(ethoxycarbonyl)-4-(4-R-phenyl)-6-methyl-3,4-di-hydropyrimidine-2(1H)-thiones I-III) was confirmed by the analytical and spectral data, which were consistent with those of the other 3,4-dihydropyrimidinethiones [1][2][3]. Thus, the behavior of the reaction components under the microwave irradiation conditions does not differ from that under the conventional heating conditions.…”
supporting
confidence: 71%
“…[ 24 ] The application of the tert -amino effect to the synthesis of pyrido-fused benzenes, pyridazines and uracils has also been reported. [ 25 - 28 ] In this approach the ring closure occurs between the β-carbon of a vinylic group possessing electron withdrawing substituents at the β-position and the α-carbon of an ortho-tert -amino group. In a recent report this ring closure method is also extended to the preparation of new spirocyclic ring systems by incorporating the β-substituents of the vinylic group into a ring [ 29 ] in this way.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the reaction of 2-piperazinobenzaldehyde 1 with cyanothioacetamide 2a in butanol for 2 h the product of tandem reactions [2], the Knoevenagel condensation and cyclization by the "tert-amino effect" mechanism [3-6], 2,3,4,41,5,6-hexahydro-1H-pyrazin[1,2-a]quinoline 3 was formed, while reaction of benzaldehyde 1 with cyanoacetamide 2b stopped at the stage of formation of the Knoevenagel condensation product 4b which did not cyclize on prolonged heating. When the reaction of 2-piperazinobenzaldehyde 1 with cyanothioacetamide 2a was carried out in toluene the vinyl derivative 4a was isolated, which on heating in butanol cyclized to the pyrazinoquinoline 3.…”
mentioning
confidence: 99%